Wollastonite-diopside-carbon composite foams from a silicone resin and inorganic fillers. Issue 1 (January 2018) - Fiocco, Laura; Agnoli, Stefano; Pedron, Danilo; Secco, Michele; Tamburini, Sergio; Ferroni, Letizia; Gardin, Chiara; Zavan, Barbara; Bernardo, Enrico
Abstract: A novel multiphasic ceramic composite was developed in the form of highly porous open-celled foams, starting from a silicone-based mixture, incorporating micro-sized fillers and fired in N2 atmosphere. Highly homogeneous mixtures were first foamed at 350 °C, in air, and later fired at 1100 °C. The process yielded a final ceramic with two silicate phases (wollastonite, CaSiO3, and diopside, CaMgSi2 O6 ), embedded in an amorphous matrix, exhibiting a particularly remarkable compressive strength (exceeding 20 MPa), and a residual open porosity of about 65% (with pore diameters ranging between 300 and 500 µm). This result cannot be attributed to the formation of a homogeneous silicon oxycarbide (SiOC) matrix; on the contrary, the amorphous material surrounding the silicate crystals consisted of a nano-composite, with C domains immersed in a silicate glass phase. Very preliminary cell culture studies performed in vitro showed encouraging results.